Challenges in health and technological literacy of older adults: a qualitative study in Isfahan - Zahra Shams-Ghahfarokhi (BMC Geriatrics, 2025)
Abstract Objective The low level of digital health literacy skills, especially among older adults, increases their risk of limited access to health services. Health literacy plays an important role in maintaining health and improving the quality of life of people, especially older adults. According to these two factors, the importance of examining the health literacy of older adults and how they use technology to improve their health is becoming increasingly clear. Method To address this, the study employed a grounded theory approach, aiming to uncover the challenges encountered by older adults in utilizing health-related technologies. To achieve this goal, semi-structured interviews were conducted with 25 older adults, selected through theoretical, targeted, and maximum variety sampling methods. Result After analyzing the data, seven main categories were identified: isolation and loneliness, resistance to change, limitation of digital literacy, health literacy gap, dependence, physical disability, and facilitating access to health-related technology. Conclusion The core category,'Seniors on the margin of digital health literacy,'was selected to encompass the other seven categories.